2018
DOI: 10.1021/acsmedchemlett.8b00413
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 12-O-Mono- and Diglycosyl-oxystearates, a New Class of Agonists for the C-type Lectin Receptor Mincle

Abstract: Fifteen glycosyl-oxystearates were synthesized by Crich's 4,6-benzylidene and Koëning−Knorr strategies. Assessment of structure−activity relationships using macrophage-inducible C-type lectin (Mincle) receptor cells expressing nuclear factor of activated T cells (NFAT)-green fluorescent protein (GFP) revealed that four dimannopyranosyl-oxystearate analogues were Mincle agonists and that 12-O-(2-O-α-D-mannopyranosyl)-α-D-mannopyranosyl-oxystearate was as an activator of both mouse and human Mincle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Nanomaterials usually refer to materials with one dimension or more within the range of 0.1-100 nm in the three-dimensional scale of tiny particles [7,8]. Fluorescent nanomaterials include organic fluorescent dyes [9], fluorescent proteins [10], QDs, MNCs, CDs, etc. Organic fluorescent dyes are the most common nano fluorescent probe materials.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials usually refer to materials with one dimension or more within the range of 0.1-100 nm in the three-dimensional scale of tiny particles [7,8]. Fluorescent nanomaterials include organic fluorescent dyes [9], fluorescent proteins [10], QDs, MNCs, CDs, etc. Organic fluorescent dyes are the most common nano fluorescent probe materials.…”
Section: Introductionmentioning
confidence: 99%
“…Only weak activity was detected for the methyl esters of the fatty acids derived from cleavage from the l -mannitol core, showing that the intact structure is required for full activity. A recent study reported Mincle signaling agonists developed from the side chains of 44-2 , but linked to 12-hydroxystearic acid …”
Section: Introductionmentioning
confidence: 99%
“…C 8 GlcC 8 This work builds on related efforts exploring structure activity relationships of acyl-hexoses (as analogues of glucose monomycolate), 15,16 glycosyloxy-stearates (as analogues of the mannosyloxymannitol glycolipid from Malassezia pachydermatis), 28 glycerolipids (as analogues of glycerol monomycolate), 27,29 mono- 13 and diacyl trehaloses, 12,30 and lipidated diaroyltrehaloses (as analogues of brartemicin). 14,31 The present work is notable for the simplicity of the resulting agonists and the fact that unlike acyl-hexoses they exist as single stereoisomers.…”
Section: Nfat-gfp (%)mentioning
confidence: 99%